Occurrence and spatial distribution of antibiotic resistance genes in the Bohai Sea and Yellow Sea areas, China. (September 2019) - Lu, Jian; Zhang, Yuxuan; Wu, Jun; Wang, Jianhua; Zhang, Cui; Lin, Yichen
Abstract: Rapid development of Bohai and Yellow Sea Economic Rim has led to the concern of emerging contamination of marine environments. This study investigated the spatial distribution of antibiotic resistance genes (ARGs) in Bohai and Yellow Sea areas. A large scale sampling from Bohai Sea, Yellow Sea and the major cities along the coastline from the mouth of Yalu River to the Yangtze River was performed. The spatial distribution of target ARGs based on the absolute abundances was in the trend of river water ≈ coastal water > the Bohai Sea > the Yellow Sea, inshore > offshore and inner bay > bay mouth. The total absolute abundances of selected ARGs in the coastal waters (1.23 × 10 4 –3.94 × 10 5 copies/mL) were about 1–4 orders of magnitude higher than those in the sea (21.1–8.00 × 10 3 copies/mL). The abundances of ARGs fluctuated greatly in the Yellow Sea and the coastal areas. Sulfonamide resistance genes hold the highest abundances in the Bohai and Yellow Sea (up to 2.13 × 10 3 copies/mL of sul 1 and 6.23 × 10 3 copies/mL of sul 2), followed by tetracycline and quinolone resistance genes, while qnr A hold the highest abundances in coastal areas (up to 3.66 × 10 5 copies/mL). The distribution coefficients of target genes between sediments and corresponding water samples were more than 1.0 in the majority of different aquatic systems. According to the principle component analysis and redundancy analysis, water samples collected from the sea clustered together while those from the coastal zone and rivers were separated. Ammonium and nitrate played important roles in the distribution and variation of ARGs. Co-occurrence network analysis revealed that the potential multi-antibiotics resistant bacteria were detected with higher abundances in the Yellow Sea than in the Bohai Sea. These observations provided a comprehensive new insight into the pollution status of ARGs in the Bohai and Yellow Sea areas. Graphical abstract: Image 1 Highlights: Pollution status of ARGs in the Bohai Sea and Yellow Sea areas was investigated. ARGs abundances in coastal areas were much higher than those in seawater. ARGs abundances fluctuated greatly in the Yellow Sea and the coastal areas. Sediments served as important reservoirs of ARGs in marine environments since Kd  > 1.0 Multi-antibiotics resistant bacteria were detected in both Bohai Sea and Yellow Sea. Abstract : This study investigated distribution and abundances of ARGs and provided comprehensive new insight on ARGs pollution in Bohai Sea and Yellow Sea areas.